Diffusive non-toxic goiter and purbatic course in girls - С. І. Турчина; В. О. Динник (Publishing House TRILIST, 2019)
Objective of the study. To study the peculiarities of the puberty course in girls with diffuse non-toxic goiter (DNG) and justify an individual approach to prevention of its disorders. Materials and methods. Compares the features of the puberty course and state of the thyroid system in girls with DNG (main group), which was first diagnosed at 9-13 years in the prepubertal period (n = 51) and early puberty (n = 58). The comparison group consisted of 107 peers with a normal thyroid volume, harmonious physical development and physiological course of puberty. An ultrasound of the thyroid gland was performed; thyroid stimulating hormone (TSH) value, free fractions of thyroxine (fT4) and free triiodothyronine (fT3) in blood were determined, TSH/fT4 ratios and fT3/fT4 ratios were calculated in conventional units. Sexual development and puberty course were also studied. Results. An individual analysis of sexual development during the initial examination allowed us to determine its normal character in 90.0% girls with disabilities, 6.4% recorded an acceleration of its pace for 1-2 years, and only 2 girls (1.8%) 13 years old were diagnosed with a slowdown pace of puberty. Two (1.8%) 10-year old girls had inverted puberty. It was found that an earlier onset of puberty occurs with an increase in TSH and fT3 levels against the background of normal fT4. Dynamics of observation showed an increase of patients with signs of thyroid failure, which was accompanied by a delay in sexual development in 11.1% and menstrual dysfunction in 28.0% girls. Conclusion. Girls with DNG identified in pre- and early puberty increase the risk of delayed sexual development and menstrual dysfunction, which is the rationale for therapy aimed at correcting and preventing the progression of thyroid dysfunction. The feasibility of using potassium iodide and/or L-thyroxine in order to prevent violations of the puberty course in girls with DNG is substantiated